ST-Elevation Myocardial Infarction in Situs Inversus Dextrocardia : A Case Report - Asri, Said; Koh, Keng Tat; Oon, Yen Yee; Siti Nadia, Che Adinan; Ong, Tiong Kiam (ASEAN Federation of Cardiology, 2016)
ST-elevation myocardial infarction (STEMI) in situs inversus dextrocardia is a rare combination and poses many challenges in terms of diagnosis and management. These include the early detection of dextrocardia as well as the interpretation of the ECG. In addition, percutaneous coronary intervention could be challenging in the setting of dextrocardia because of diffi culty in cannulating the coronary arteries, selection of catheters, catheter manipulation, image acquisition and interpretation.